2022
DOI: 10.1111/1365-2435.14213
|View full text |Cite
|
Sign up to set email alerts
|

Widespread variation in functional trait–vital rate relationships in tropical tree seedlings across a precipitation and soil phosphorus gradient

Abstract: A fundamental assumption of functional ecology is that functional traits are related to interspecific variation in performance. However, the relationship between functional traits and performance is often weak or uncertain, especially for plants. A potential explanation for this inconsistency is that the relationship between functional traits and vital rates (e.g. growth and mortality) is dependent on local environmental conditions, which would lead to variation in trait–rate relationships across environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that soil nutrients are among the vital factors that impact seedling recruitment (Bentos et al, 2013;Martini et al, 2020). Additionally, a study of seasonally moist tropical forests in Panama showed that variations in the relationships of functional traits and vital rates could be explained by soil phosphorus (Browne et al, 2023). In the post-JOW period, factors impacting the functional traits of current year seedlings shifted from soil nutrients to the amount of litterfall.…”
Section: Effects Of Environmental Conditions On Seedling Functional T...mentioning
confidence: 98%
“…Previous studies have demonstrated that soil nutrients are among the vital factors that impact seedling recruitment (Bentos et al, 2013;Martini et al, 2020). Additionally, a study of seasonally moist tropical forests in Panama showed that variations in the relationships of functional traits and vital rates could be explained by soil phosphorus (Browne et al, 2023). In the post-JOW period, factors impacting the functional traits of current year seedlings shifted from soil nutrients to the amount of litterfall.…”
Section: Effects Of Environmental Conditions On Seedling Functional T...mentioning
confidence: 98%